Pendampingan Pengembangan Desa Wisata Menuju Legalisasi Berbasis Pentahelix di Kabupaten Karawang - Fajrin, Yeni; Sumarni, Neni; Arisandi, Vidya (Yayasan Kawanad, 2025)
The community engagement program for developing tourism villages in Karawang Regency aimed to strengthen local capacity in the legalization process through a participatory pentahelix approach. This framework integrates collaboration among academics, local government, entrepreneurs, communities, and the media to establish an adaptive and sustainable governance system. The study employed a qualitative descriptive method with a participatory model emphasizing experiential learning. The program involved 33 participants from eleven partner villages, covering stages of socialization, thematic training, technical assistance, and evaluation. The results revealed an 85% increase in participants’ understanding of tourism village legalization standards, nine villages successfully drafted preliminary tourism village profiles aligned with the Ministry of Tourism and Creative Economy’s indicators, and multi-stakeholder collaboration strengthened the institutional process. These findings indicate that the pentahelix approach not only enhances administrative readiness but also reinforces the role of local communities as primary agents of community-based tourism. Despite its success, the short duration and wide coverage remain constraints, suggesting the need for extended assistance and digital capacity development. The program is expected to accelerate tourism village legalization in Karawang and serve as a replicable model for sustainable local tourism development.